Diseño de un sistema contable para el centro Naturista VIDA SANA del cantón Caluma – Provincia Bolívar. - Tenecota Valladares, Teresa (2012)
The Naturist Center "Fitness" starts its activities in the City of Caluma in January 2007; in nearly five years of a system it never applied Accounting to let you know for sure the state in which it is located, its heritage and whether it is profitable. This allows the respective research by applying a survey of the owner of the premises agrees to provide information and implement the new system promises to propose, considering the absence of this prevents timely, reliable information and see to take decisions. The lack of records and accounting control, makes the owner does not know As has invested, how much money you actually have, or the stock of products and drugs available. The purpose of this work is to design and implement a system Accountant or Accounting Software that allows the Naturist Center "Fitness" know your financial status and take action. If we consider that the accounting system is a set of procedures, records and equipment made available to the microenterprise permanently to know their status and financial position, to take corrective or improvement; it is known that constitutes a weapon powerful to succeed. After the diagnosis made, it is recommended: to develop and implement in the form immediately the accounting system "Monica 8.5" according to the sales activity products and natural medicines; which comprises the Journal Book, Records Accountants, Proof of Income and Expenses, Invoices, Reporting and Accounting other tools that give to know about the financial status of the Microenterprise. This new system has many advantages, among which we note: ideal for this type of business because invoice, inventory controls, performs list Prices and only need to install it, have on hand a laptop or put it on net, it is easy to install and does not require who operates large accounting skills. It should also be noted that this new accounting system creates Invoices, Inventory, Kardex, Accounts Receivable, Financial Statement, Accounts Payable; and everything related to accounting to know the status of microenterprise minute minute. This proposal is already being applied successfully in the Naturist Center "Life Sana "Caluma City. The new accounting system "Monica 8.5" has radically changed the mission, vision and goals of microenterprise and it shows from and progress and a certainty know what you have in merchandise and money. More research work to show the problem, let find right tool to know at any moment the financial status and take right decisions to improve business.